Molecular dynamics and Monte Carlo simulations of the sputtering of a nanoporous solid - Rodriguez Nieva, J. F. (2013)
We calculate the sputtering induced on a nanoporous material by fast penetrating ions, such as those used for track formation and surface modification, in order to better understand and quantify the ejection and redeposition of atoms in open cell nanofoams. We model the ion-induced sputtering yield from a porous solid using a Monte Carlo approach and compare the results for the sputtering yields, angular and depth distributions of the ejecta, with Molecular dynamics simulations and find good agreement. For certain foam geometries, our simulations predict enhanced sputtering yields compared to the yields from a fully dense solid.